Parameters optimization of crop protection UAS based on the first industry standard of China - Zhang, Songchao; Qiu, Baijing; Xue, Xinyu; Sun, Tao; Peng, Bin (International Journal of Agricultural and Biological Engineering, 2020)
The effective swath width (ESW) and the droplet penetration rate (DPR) directly affect the spraying quality, the spraying efficiency and the control effect of pests and diseases during the crop protection unmanned aircraft system (CPUAS) application. However, the ESW and DPR are not constant with the changes of the flight speed (FS) and the flight height (FH). In order to investigate the ESW and DPR of the CPUAS P20, four levels of FS (3 m/s, 4 m/s, 5 m/s and 6 m/s) and three levels of FH (1.5 m, 2.0 m and 2.5 m) experiments were carried out according to the first industry standard of China for the CPUAS in the wheat field. The results demonstrated that the ESWs were negatively correlated with the FS and the FH. Most of the ESWs were over 2 m in the 12 treatments, in which the maximum one was 3.25 m (3 m/s, 1.5 m). The DPRs were negatively correlated with the FH under the same FS, the average value of the DPRs was 48.37%, in which the maximum one was 78.34% (4 m/s, 1.5 m) and the minimum one was 25.5% (6.0 m/s, 2.5 m). The statistical analyses showed that the FS had significant impacts on the ESWs (0.01<p-value<0.05) while there were no significant differences among different FH treatments (p-value >0.05). The impacts of both FS and FH on the DPRs were extremely significant (p-value<0.01), and the interactive impacts were significant (0.01<p-value<0.05). Therefore, it is concluded that reducing the FS could increase the ESWs, and reducing the FH could increase the DRPs at the same FS. In conclusion, the maximum spraying efficiency of P20 was 4.342 ha/h with 6 m/s FS and 1.5 m FH in case of satisfying the requirement of DPRs. This study provided scientific references for guiding the CPUAS spraying.Keywords: crop protection unmanned aircraft system, standard, effective swath width, penetration, parameter optimizationDOI: 10.25165/j.ijabe.20201303.5439Citation: Zhang S C, Qiu B J, Xue X Y, Sun T, Peng B. Parameters optimization of crop protection UAS based on the first industry standard of China. Int J Agric & Biol Eng, 2020; 13(3): 29–35.